Shareholder Remedies: Demise of the Derivative Claim? - Julia Tang (UCL Journal of Law and Jurisprudence, 2015)
The new statutory derivative claim in the Companies Act 2006 ("CA 2006") was meant to herald a more modem, flexible and accessible criteria for determining whether a shareholder could pursue an action. It was aimed at tackling the problematic rules which emerged from Foss v Harbottle (1843). This paper examines the twostage procedure in the CA 2006 Part 11 by focusing on specific elements within it, i.e., prima facie case, ratification etc. The complexities of pursuing a statutory derivative claim will be highlighted by critically discussing how these elements have been interpreted in recent case law such as Franbar Holdings Ltd v Patel (2008) and Stainer v Lee (2010). It will be argued that the uncertainty that presently plagues the two-stage procedure and the interpretation of the elements within it is likely to lead to the demise of the statutory derivative claim in England and Wales for the foreseeable future. Read more